Mediasi Penal Sebagai Bentuk Penanganan Perkara Anak - Ringgi Sarungallo; Ramlani Lina Sinaulan; Mohamad Ismed (Universitas Jayabaya, 2023)
Dispute resolution with mediation is an alternative of problems solving in society. In the concept of the current developments of the Judiciary, the procedure for handling criminal cases in several countries has been known for penal mediation. Penal mediation is an alternative settlemen of criminal cases emphasizing restorative justice approach, which is carried out between the victim and the offender or his/her family with the purpose of the restoring the balance in the society. This study aims to analyze how to the implementation of penal mediation children criminal cases with type of research is an literature approach. The presence of penal mediation is deemed necessary by the community as a means of resolving of chidren criminal cases that are fast, economical, and acceptable by parties outside the court so as to achieving a win win solution and will bring justice to perpetrators and victims. The application of penal mediation for the purpose of achieving Pancasila justice.